Comparative Study of Management Between Partial Turbinectomy and Submucous Diatheramy - Mohammad lqbal, Dileep Kumar, Noor Alam Ansari (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: Comparative study between partial turbinectomy and submucous diathermy (SMD) to observe merit and demerit of management of chronic inferior turbinate hypertrophy. Study Design: Comparative study. Place & Duration: Department of Otolaryngology PUMHS Nawabshah, from April 2010 to March 2011. Material and Methods: Fifty consecutive patients were included as per inclusion and exclusion criteria, all having bilateral inferior turbinate hypertrophy with nasal obstruction. We divided patients in two equal half as groups A and B according to surgical procedures. In group A, partial turbinectomy was done, while in group B submucous diathermy was applied. Post operative follow-up was carried out on 01 week than, 1, 3, 6 months assessments. Results: In group B 80% improvement of nasal air flow was seen while 98% in group A. Postoperative hemorrhage was not seen in submucous diathermy cases and 2% hemorrhage was seen in partial turbinectomy. Edema and pain was recorded in S.M.D cases. Wile nasal crust, pain and bleeding were observed in group A. Conclusion: Different surgical techniques are used for the management of chronic inferior turbinate hypertrophy, but partial turbinectomy is more effective one in our study.